TELAAH KOMPARATIF REDAKSI TASYAHUD VERSI SUNAN AL-NASA’I - Zainuddin (Institut Agama Islam Darul Ulum Kandangan, 2025)
Sunan al-Nasa'i reports fourteen (14) hadiths about the wording of the tashahhud (hadith numbers 1162-1175) with various chains of narration from the generation of the tabi'in/tabi' al-tabi'in, but all of them are sourced from four (4) Companions of the Prophet, namely: Ibn Mas'ud, Abu Musa al-Ash'ari, Ibn 'Abbas and Jabir bin Abdullah. Furthermore, nine (9) different chains of narration – eight hadiths referring to Ibn Mas'ud and one hadith referring to Jabir – report the following identical wording of the tashahhud. Al-Ta?iyy?tu lill?h, wa al-?alaw?tu, wa al-?ayyib?t. Al-sal?mu ?alayka ayyuh? al-nabiyyu wa ra?matull?hi wa barak?tuh. Al-sal?mu ?alayn? wa ?al? ?ib?dill?hi al-??li??n. Ashhadu an l? il?ha illa All?h, wa ashhadu anna Mu?ammadan ?abduhu wa ras?luh. In addition, hadith number 1165, which also refers to Ibn Mas'ud, indicates the same wording of the tashahhud. Meanwhile, different wordings of the tashahhud are found in four (4) hadiths: 1. One hadith referring to Ibn Mas'ud (number 1168), 2. One hadith referring to Ibn 'Abbas (number 1174), and 3. Two hadiths with separate chains of narrations cited in Abu Musa al-Ash'ari as the primary source (numbers 1172 and 1173).